The role of reactive oxygen species (ROS) and cytochrome P-450 2E1 in the generation of carcinogenic etheno-DNA adducts - Linhart, Kirsten-Berit; Bartsch, Helmut; Seitz, Helmut K. (Redox Biology, 2014)
Exocyclic etheno-DNA adducts are mutagenic and carcinogenic and are formed by the reaction of lipidperoxidation (LPO) products such as 4-hydoxynonenal or malondialdehyde with DNA bases. LPO products are generated either via inflammation driven oxidative stress or via the induction of cytochrome P-450 2E1 (CYP2E1). In the liver CYP2E1 is induced by various compounds including free fatty acids, acetone and ethanol. Increased levels of CYP2E1 and thus, oxidative stress are observed in the liver of patients with non-alcoholic steatohepatitis (NASH) as well as in the chronic alcoholic. In addition, chronic ethanol ingestion also increases CYP2E1 in the mucosa of the oesophagus and colon. In all these tissues CYP2E1 correlates significantly with the levels of carcinogenic etheno-DNA adducts. In contrast, in patients with non-alcoholic steatohepatitis (NASH) hepatic etheno-DNA adducts do not correlate with CYP2E1 indicating that in NASH etheno-DNA adducts formation is predominately driven by inflammation rather than by CYP2E1 induction. Since etheno-DNA adducts are strong mutagens producing various types of base pair substitution mutations as well as other types of genetic damage, it is strongly believed that they are involved in ethanol mediated carcinogenesis primarily driven by the induction of CYP2E1.
Gesehen am 20.10.2020